A Study of Database Models for Social Network Analysis - Salgueiro, Mariana D. A.; Lifschitz, Sérgio; Haeusler, Edward Hermann; dos Santos, Verônica; Heine, Alexandre A. P. (Anais do Simpósio Brasileiro de Banco de Dados (SBBD); 2022: Anais do XXXVII Simpósio Brasileiro de Bancos de Dados, 2022)
This paper discusses conceptual and logical data models for social media datasets and applications. On the one hand, we focus on the data representation requirements from the available APIs of some social network systems. On the other hand, we consider those application requirements for information manipulation. We propose a conceptual meta-model and one possible instantiation. We also give preliminary practical results considering relational and graph database systems.